On-Surface Synthesis Proceedings of the International Workshop On-Surface Synthesis, École des Houches, Les Houches 25-30 May 2014 - Gourdon, André; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
With contributions by leading international experts, this book presents a detailed compilation of a new and very active field. It is the first book devoted to the covalent coupling of molecular precursors on surfaces that allows the preparation of 0D, 1D and 2D molecules that cannot be synthesized in solution. This book is aimed at students and researchers interested in nanochemistry and molecular devices and it gives the reader a pedagogical up-to-date vision of the most recent developments. The editor ensures a multidisciplinary approach involving molecular chemistry, surface sciences, surface spectroscopies, theory, scanning tunneling and non-contact atomic force microscopies.
The Emergence of Covalent On-Surface Polymerization -- Transition Metals Trigger On-Surface Ullmann Coupling Reaction: Intermediate, Catalyst and Template -- On-Surface (Cyclo-)dehydrogenation Reactions: Role of Surface Diffusion -- Enediyne Cyclization Chemistry on Surfaces under Ultra-High_Vacuum -- On-Surface Synthesis by Azide-Alkyne Cycloaddition Reactions on Metal Surfaces -- On-Surface Synthesis of Phthalocyanine Compounds -- Molecular on-surface synthesis: Metal Complexes, Organic Molecules and Organometallic Compounds -- On-Surface Synthesis of Single Conjugated Polymer Chains for Singe-Molecule Devices -- On-Surface Synthesis on Insulating Substrates -- Bottom-up Fabrication of Two-Dimensional Polymers on Solid Surfaces -- On-Surface Dynamic Covalent Chemistry -- Synthesis of Atomically Precise Graphene-Based Nanostructures: A Simulation Point of View -- Formation Mechanisms of Covalent Nanostructures from Density Functional Theory.
Keywords: Nanochemistry; Nanoscience; Surfaces (Technology).; Thin films; Polymers; Chemistry, Physical and theoretical; Nanochemistry; Nanophysics; Surfaces, Interfaces and Thin Film; Polymers; Theoretical Chemistry